Extensive Reading in the Second Language Classroom - Day R. R. Richard (Cambridge Language Education)
This comprehensive examination of extensive reading shows how reading large quantities of books and other materials can provide students with essential practice in learning to read as well as help them to develop a positive attitude towards reading that is sometimes missing in second language classes. The authors first examine the cognitive and affective nature of reading and the nature of good reading material, which they term Language Learner Literature. They then offer a wealth of practical advice for implementing extensive reading with second language learners. Suggestions are provided for integrating extensive reading into the curriculum, establishing a library, writing and selecting reading material, and keeping records for purposes of evaluation. The text also describes a wide variety of classroom activities to supplement individualized silent reading. This book will be useful for authors of reading material, pre-service teachers, and teachers and administrators who want to improve the teaching of reading in their second language programs.Richard R. Day is Professor of English as a Second Language and Second Language Acquisition in the ESL Department at the University of Hawaii. Julian Bamford is Associate Professor in the School of Information and Communications at Bunkyo University in Japan.